2020
DOI: 10.3389/fgene.2020.565955
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis Extracts a Core ceRNA Network of the Fetal Hippocampus With Down Syndrome

Abstract: Accumulating evidence suggests that circular RNAs (circRNAs)—miRNA–mRNA ceRNA regulatory network—may play an important role in neurological disorders, such as Alzheimer’s disease (AD). Interestingly, neuropathological changes that closely resemble AD have been found in nearly all Down syndrome (DS) cases > 35 years. However, few studies have reported circRNA transcriptional profiling in DS cases, which is caused by a chromosomal aberration of trisomy 21. Here, we characterized the expression profiles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Finally, circRNA-miRNA-mRNA networks in different memory stages were established according to ceRNA theory. Dysfunctional circRNA-miRNA-mRNA regulatory networks represent an essential layer of epigenetic control in central nervous system disorders (Wang et al, 2020 ). Given the bioinformatics analysis results and ceRNA networks, our study identified 14 circRNAs, 2 miRNAs, and 4 mRNAs involved in memory extinction and retrieval-extinction in mice, which constituted 2 ceRNA networks.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, circRNA-miRNA-mRNA networks in different memory stages were established according to ceRNA theory. Dysfunctional circRNA-miRNA-mRNA regulatory networks represent an essential layer of epigenetic control in central nervous system disorders (Wang et al, 2020 ). Given the bioinformatics analysis results and ceRNA networks, our study identified 14 circRNAs, 2 miRNAs, and 4 mRNAs involved in memory extinction and retrieval-extinction in mice, which constituted 2 ceRNA networks.…”
Section: Discussionmentioning
confidence: 99%
“…Dang et al studied human embryonic development and found that there were 1,032 types of circRNAs in the exon region of 2,974 genes in cells (endocell clusters, nourishing ectoderm cells, etc.) at different developmental stages [15]. Most circRNAs can perform specific dynamic regulation during embryonic development and are mainly involved in the regulation of material metabolic pathways in early embryonic development [15].…”
Section: Circrnas Regulate Fetal Development In Livestockmentioning
confidence: 99%
“…at different developmental stages [15]. Most circRNAs can perform specific dynamic regulation during embryonic development and are mainly involved in the regulation of material metabolic pathways in early embryonic development [15]. 3 BioMed Research International detect the expression of circRNAs [14].…”
Section: Circrnas Regulate Fetal Development In Livestockmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] With the development of gene expression profiles, bioinformatics have become most common used strategies to screen key biomarkers in a variety of diseases including DN. [1,7,8] TGFβ1 is reported to be differentially expressed in DN and may participate in the development of DN. [9] Xu et al find hub genes associated with DN using data, and identify 13 hub genes including C3, FN1, COL1A2, LUM, THBS2, CD44, LYZ, FOS, EGR1, ALB, PLG, EGF, and DUSP1.…”
Section: Introductionmentioning
confidence: 99%